Overview of Techniques for State of Charge Estimation in Lithium-Ion Batteries and Future Directions - Errifai Nidale; Rachid Aziz; Boudmane Bilal; Mortabit Idriss (EPJ Web of Conferences)
As Li-ion batteries age, estimating the exact state of charge (SOC) becomes more difficult due to the non-linear behavior of their components. Achieving precision while maintaining robustness and uncomplicated implementation remains of utmost importance. Much research in recent years has focused on studying and benchmarking various SOC estimation techniques tailored to commercial LiBs. This work emphasizes different SOC estimation methods, particularly model-based and AI approaches. The paper's main objective is to provide a comprehensive analysis of advanced hybrid SOC estimation techniques, a synthesized cross-analysis of the most recent studies, and a series of practical recommendations for future work.